Public-private partnership: institutional background and trends in the Republic of Belarus - Galina Yasheva (Vestnik of Vitebsk State Technological University, 2015)
The paper studies trends in the development of the Institute of Public-Private Partnership in the Republic of Belarus on the basis of the clarification of the conceptual apparatus of public-private partnerships and research institutional preconditions. The subject of the research is the relationship of public- private partnership.